2019
DOI: 10.1186/s12871-019-0912-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low dose naloxone on the immune system function of a patient undergoing video-assisted thoracoscopic resection of lung cancer with sufentanil controlled analgesia — a randomized controlled trial

Abstract: BackgroundPerioperative immune function plays an important role in the prognosis of patients. Several studies have indicated that low-dose opioid receptor blockers can improve immune function.MethodsSixty-nine patients undergoing video-assisted thoracoscopic resection of the lung cancer were randomly assigned to either the naloxone group (n = 35) or the non-naloxone group (n = 34) for postoperative analgesia during the first 48 h after the operation. Both groups received sufentanil and palonosetron via postope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…Finally, pharmacogenomics was used to predict potential drugs. Since naloxone has been approved for clinical treatment of lung cancer [ 10 ], our results may support the use of CREB1 gene status as an ovarian cancer biomarker and precision treatment of OV patients with naloxone.…”
Section: Introductionsupporting
confidence: 61%
“…Finally, pharmacogenomics was used to predict potential drugs. Since naloxone has been approved for clinical treatment of lung cancer [ 10 ], our results may support the use of CREB1 gene status as an ovarian cancer biomarker and precision treatment of OV patients with naloxone.…”
Section: Introductionsupporting
confidence: 61%
“…As for the reason for R2 resection, 59.5% ( n = 22) cases were due to bulky metastatic lymph nodes which could not be completely resected. Additionally, postoperative immunosuppression may further contribute to the progression of residual disease 22,23 . For patients with R2 resection in our study, even postoperative radiotherapy could not make up for compromised patient survival following incomplete resection.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, postoperative immunosuppression may further contribute to the progression of residual disease. 22,23 For patients with R2 resection in our study, even postoperative radiotherapy could not make up for compromised patient survival following incomplete resection. Therefore, for most of the patients with clinical stage N2, especially those with bulky metastatic lymph nodes, the conclusion is that optimal treatment is concurrent chemoradiotherapy rather than surgery.…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, it was reported that opioid receptor antagonists, e.g., NAL, at low doses, enhance the release of endogenous opioids, as well as upregulate opioid receptors [ 81 , 82 ]. Interestingly, low-dose NAL administered to a patient under sufentanil-controlled analgesia increased levels of opioid growth factor (OGF), which is an endogenous opioid, and natural killer (NK) cells, a critical player in innate immunity [ 83 , 84 ]. Other studies also showed that OGF increases numbers of NK cells [ 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%